The CVaR constrained stochastic programming ALM model for defined benefit pension funds. (12th October 2009) - Bai, Manying; Ma, Jie
In this paper, a model for finding optimal contribution rates and portfolio allocations takes into account the funding situation of the fund. Using the CVaR risk measure, the model can be solved with dynamic stochastic programming techniques. Our model improves Kouwenberg's and Bogentoft's dynamic stochastic programming ALM model. And by adding CVaR constraints and considering the real situation of pension funds in China, we ultimately construct a new ALM model on DB enterprise pension funds. We build two models according to two different periods within the initial time and the stable period of pension funds and through optimisation methods to analyse the optimal investment strategy and obtain some useful conclusions.